Semantic Analysis from Toshihiko Izutsu's Perspective on the Meaning of Jihad in the Qur'an - Ulwan, Abdullah Nasih; Nugroho, Kharis (Universitas Muhammadiyah Surakarta, 2024)
This study aims to explore the meaning of jihad in the Qur'an using Toshihiko Izutsu's semantic approach, which emphasizes the importance of word relationships within semantic networks and historical contexts. Employing a qualitative method based on textual studies, this research analyzes Qur'anic verses containing the term jihad through syntagmatic and paradigmatic approaches. Data were taken from verses such as Surah At-Taubah (9:20, 9:41), Surah Al-Ankabut (29:69), and Surah Al-Hajj (22:78), using classical references like Mufradat Alfadz al-Qur'an by Al-Raghib Al-Isfahani and Lisan al-Arab by Ibn Manzur. The findings indicate that jihad is a multidimensional concept encompassing spiritual, moral, and social dimensions. Collocations such as jihad fi sabilillah and jihad with wealth and self emphasize devotion to Allah, while its relationships with terms like qital (war), sabr (patience), and hijrah (migration) enrich the semantic network of jihad. Diachronically, the concept evolved from a secular understanding during the pre-Qur'anic era to an ethical and spiritual concept in the Qur'anic period and was later institutionalized in Islamic law post-Qur'anic period. This study contributes to enriching Qur'anic studies by offering a holistic analytical framework, helping correct misinterpretations of jihad, and supporting Islamic education through a more contextual understanding. Future studies are recommended to involve empirical data, classical exegesis, and other linguistic approaches to broaden perspectives.